Entropy generation analysis of hydrate dissociation by depressurization with horizontal well in different scales of hydrate reservoirs. (15th April 2017) - Feng, Jing-Chun; Wang, Yi; Li, Xiao-Sen
Abstract: Based on the hydrate conditions of the South China Sea, hydrate samples were synthesized in the Cubic Hydrate Simulator (CHS) and the Pilot-Scale Hydrate Simulator (PHS), and hydrate dissociation experiments by depressurization with single horizontal well were carried out. In order to illuminate the characteristic of the irreversible energy loss during the gas production process in a large-scale hydrate simulator and a smaller hydrate simulator, the entropy generation model was established. Results show that the evolutions of the pressure, temperature, gas production, and water production during hydrate dissociation process with different scales of hydrate reservoir are similar. Moreover, entropy generation in the mixed gas release stage is the largest. In addition, in the dissociated gas release stage, the ratio of entropy generation decreases remarkably with the increase of the hydrate reservoir scale, and constant-pressure depressurization method is favorable for hydrate dissociation in a larger scale hydrate reservoir. Highlights: Hydrate dissociation by depressurization in different-scale reservoirs was executed. Single horizontal well was performed for production well. Entropy generation model during depressurization process was established.